Adjustments for oral fluid quality and collection methods improve prediction of circulating tetanus antitoxin: Approaches for correcting antibody concentrations detected in a non-invasive specimen. Issue 2 (8th January 2021) - Garrison-Desany, Henri; Ochieng, Benard Omondi; Odiere, Maurice R.; Kuo, Helen; Gibson, Dustin G.; Were, Joyce; Kagucia, E. Wangeci; Pasetti, Marcela F.; Kim, Hani; Reymann, Mardi; O'Brien, Katherine; Hayford, Kyla
Abstract: Objectives: To examine whether anti-tetanus toxoid (anti-TT) immunoglobulin G (IgG) levels measured in oral fluid and adjusted for collection difficulties and specimen quality are associated with total IgG and anti-TTIgG in oral fluid and assess if statistical adjustment for them improves prediction of anti-TT IgG in serum. Methods: 267 children, ages 12 to 15 months, enrolled in the M-SIMU randomized controlled trial participated in this nested cross-sectional analysis. Venous blood and oral fluid (OF) specimens were collected, and OF collection difficulties such as crying or gagging were recorded. OF volume was documented and total IgG was measured in OF specimens and anti-TT IgG was measured in OF and serum by enzyme immunoassay (EIA). Collection difficulties, volume and sociodemographic characteristics were assessed in relation to total IgG and anti-TT IgG in OF via multivariate regression. These models were extended to evaluate the association between anti-TT IgG in OF and in serum. A prediction model was developed to adjust anti-TT IgG in OF estimates as proxy for serum. Results: Blood in the specimen, sores in the mouth and crying were positively associated with total IgG concentration while high oral fluid volume and sucking on the swab were inversely associated. None were significant predictors of anti-TT IgG in OF after adjusting for total IgG (geometric mean [GM] ratio: 1.99; 95% confidence interval: 1.78–2.24) and vaccination history (GM ratio: 2.44; 95% CI: 1.98–3.01). When predicting anti-TT IgG levels in serum with OF, total IgG modified the effect of anti-TT IgG in OF. Conclusions: Anti-TT IgG in OF is a good proxy for levels in serum, after controlling for total IgG in the specimen and other variables. Post hoc adjustments for OF volume and total IgG concentration are an important consideration when conducting serosurveys with oral fluid.